Technological progress, the "User Cost of Money," and the real output of banks - Susanto Basu; J. Christina Wang (Federal Reserve Bank of Boston, 2013)
Financial institutions provide their customers a variety of unpriced services and cover their costs through interest margins - the interest rates they receive on assets are generally higher than the rates they pay on liabilities. In particular, banks pay below-public-market interest rates on deposits while charging above-public-market rates on loans. Various authors have suggested that this situation allows one to measure the real quantity of financial services provided without explicit prices as proportional to the real stocks of financial assets held by households. We present a general-equilibrium Baumol-Tobin model where households need bank services to purchase consumption goods. Bank deposits are the single medium of exchange in the economy. The model shows that financial services are proportional to the stocks of assets only under restrictive conditions, including the assumption that either all technologies are constant or banks' technology grows at the same rate as technology in the nonfinancial economy while relative technologies of other financial institutions possibly decline. In contrast, measuring real financial output by directly counting the flow of actual services is a robust method unaffected by unbalanced technological change.
Keywords: D24; E41; O47; D91; 330